Pengaruh Work-Life Balance dan Motivasi Kerja terhadap Kepuasan Kerja melalui Stres Kerja - Widia Gusmiati; M. Afuan .; Deni Saputra (CV. ITTC INDONESIA, 2026)
This study aims to examine the influence of Work-Life Balance and Work Motivation on Job Satisfaction, with Work Stress as an intervening variable, among employees of the Vocational Training and Productivity Center (BPVP) Padang. This study uses a quantitative approach with Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis using SmartPLS. The population and sample consisted of 60 employees, selected using a saturated sampling technique. The results show a positive and significant effect of Work-Life Balance and Work Motivation on Job Satisfaction, and a negative and significant effect of Work-Life Balance on Work Stress. However, Work Motivation has no significant effect on Work Stress, Work Stress has no significant effect on Job Satisfaction, and Work Stress does not mediate the effect of Work-Life Balance or Work Motivation on Job Satisfaction.